The Use of Google Forms as Interactive Media in Teaching Hajj Material to 9th Grade Students at SMP 16 Semarang and Its Effect on Learning Interest - Saman, Miss Fatihah; Raharjo , Raharjo (Journal Corner of Education, Linguistics, and Literature, 2024)
This study examined the use of Google Forms based on interactive media in the Hajj material for grade 9 students at SMP 16 Semarang and its impact on students' learning interest. The use of Google Forms is expected to enhance student engagement in Islamic Religious Education (PAI) learning. The study adopts a quasi-experimental design with a one-group pretest-posttest method, involving two groups of students: the experimental group using Google Forms and the control group not using it. The analysis results indicate that the use of Google Forms significantly improved students' learning interest, as reflected by the increase in posttest scores in the experimental class compared to the control class. Positive impacts were also seen in the improvement of learning motivation, with students using Google Forms showing higher involvement in the learning process. Overall, this study shows that the application of interactive media such as Google Forms can enhance students' interest and engagement in PAI learning, especially in the Hajj material.